AB0502 Drug survival analysis of tofacitinib in patients with rheumatoid arthritis. (12th June 2018) - Karakoc, Y.; Ercan, I.
Abstract : Background: The drug survival rate of tofacitinib in patients with Rheumatoid Arthritis (RA) has not been reported so far. Objectives: To determine the tofacitinib drug survival rate and the factors that may affect it in patients with RA from a single rheumatology clinic. Methods: We have retrospectively analysed the track records of RA patients to whom tofacitinib was prescribed between June 2014 to December 2017. Descriptive analysis includes sex, duration of disease, autoantibody association, smoking, major trauma exposure, initiation in DMARD/ Anti-TNF resistant patients, monotherapy/ use in combination with DMARD. According to the duration of the disease, the patients were grouped as early (0–4 year), established (5–10 year), and late RA (>10 year). Drug survival was estimated using Kaplan-Meier survival analysis, and the independent variables that may affect the discontinuation were investigated by log-rank test and modelled by Backward Stepwise Cox regression analysis. Tofacitinib was prescribed to patients who were resistant to at least three different types of csDMARDs. Low- dose Steroid (below 10 mg) and NSAID drugs were used as needed. Results: During the study period, 192 (163 F, 85%) patients were prescribed tofacitinib in our clinic. Median age was 56 21–81 years, the median age at onset was 45 6–72 years, and median disease duration was 10 1–40 years. In this study, the ratio of RF and anti-CCP positivity were 63% and 60%, respectively. 33% of patients were seronegative. The patients with a smoking history were 26%, and exposure to major trauma was 16%. 15% of patients were early, 31% established, and 54% late Ra. Tofacitinib was prescribed in 92 (48%) bio-naive and 100 (52%) bio-experienced patients. It was used as monotherapy in 112 (58%) and in combination with csDMARDs 80 (42%). The drug survival rates in Kaplan Meier analysis were 77% at 3rd, 69% at 6th, 62% at 12th, 54% at 18th and 49% at 24th, 49% at 30th months. Tofacitinib was discontinued in 51 (27%) patients due to no response and in 22 (11%) patients due to side effects. None of the independent variables in regression analysis showed a relationship to tofacitinib discontinuation (p>0.05). During the follow-up period, one patient had breast cancer, and one had recurrent pneumonia. There were no tuberculosis or shingles cases reported. Two patients died from pulmonary thromboembolism. Conclusions: We found that drug survival rates of tofacitinib in RA patients were 77% at 3rd month, 69% at 6th month, 62% at 12thmonth, 54% at 18th month and 49% at 24th month, 49% at 30th months. The main cause of discontinuation of the drug was inefficiency and the loss of efficiency. We could not find any link between the predetermined independent variables and the drug discontinuation. This result raises questions about why the drug loses its efficacy in some patients in time, and how this could be preventable. Acknowledgements: One of the theories of autoimmunity is that Damage -Associated Molecular Patterns (DAMPs) may give rise to autoimmune inflammation. We were curious about how many of patients suffered from major trauma, which was defined as accidents terminated with fractures and dislocations or falls from a height of at least three metres. Disclosure of Interest: None declared